(untitled) (Student’s Journal of Health Research Africa, 2025)
Background: Lens-induced glaucoma (LIG) remains an important cause of avoidable visual morbidity in developing regions, particularly where delayed cataract extraction is common. Elevated intraocular pressure (IOP), uveal inflammation, and optic nerve compromise contribute significantly to poor outcomes. Early identification and timely surgical intervention are critical. Objectives: To evaluate the clinical profile, etiological patterns, preoperative IOP characteristics, intraoperative events, and postoperative visual outcomes in patients with LIG undergoing cataract surgery. Methods: This prospective observational study included 50 consecutive patients diagnosed with LIG at a tertiary eye hospital. Detailed clinical examination, IOP measurement, etiological classification, and B-scan evaluation were performed. All patients underwent small-incision cataract surgery with IOL implantation, followed by standardized postoperative care. Visual acuity and IOP were recorded up to six weeks. Statistical analysis was conducted using Chi-square tests, with p < 0.05 considered significant. Results: Phacomorphic glaucoma constituted 68% of cases, followed by phacolytic glaucoma at 24%. A total of 54% of patients presented with IOP > 40 mmHg. Posterior capsular rent with vitreous loss occurred in 12% of surgeries. At six-week follow-up, 44% achieved good visual acuity (6/6–6/12), whereas 22% had vision worse than 6/60. Early presentation (<1 week) and lower preoperative IOP were strongly associated with favourable visual outcomes (p = 0.001 and p = 0.04, respectively). Delayed presentation correlated with poorer vision and higher postoperative inflammation. Conclusion: Timely diagnosis and early cataract extraction significantly improve visual recovery and IOP stabilization in LIG. Elevated preoperative IOP, delayed presentation, and intraoperative complications remain major determinants of poor outcomes. Recommendations: Greater emphasis on community-based cataract screening, patient education on early symptom recognition, and prompt referral pathways are essential. Strengthening peripheral eye-care services, improving accessibility to cataract surgery, and training healthcare workers to identify early lens changes may reduce the incidence of LIG.